Reflect and develop: A pilot study to explore perceptions and to test the impact of a short course on reflective practice amongst dental practitioners undertaking continuing professional. (27th February 2021) - Nasseripour, Melanie; Gallagher, Jennifer; Ranauta, Amitha
Abstract: Introduction: In 2018, the General Dental Council introduced reflective practice as part of an Enhanced Continuing Professional Development (ECPD) system, mandatory for registrants in the United Kingdom. The aim of this pilot study was to investigate dental professionals' perceptions and practice of reflection and to explore the benefits of an evidence‐informed reflective practice learning course. Material and methods: This study was conducted at two dental schools in the United Kingdom (UK). A short course on reflective practice which included pre‐ and post‐course surveys, using closed‐ and open‐ended questions, was afforded to dental professionals attending Continuing Professional Development (CPD) courses. Quantitative data were analysed using SPSS version 25.0 software, and responses to open‐ended questions were explored by content analysis. Results: Fifty‐two dentists attending the short course provided responses; the majority were female (73%, n = 38) and internationally qualified (60%, n = 31). The pre‐course questionnaire revealed that the majority of participants (94%; n = 49) considered reflection as part of their professional practice, with 55% (n = 29) reporting doing so daily. Most (88%; n = 46) had received no formal training. The post‐course questionnaire revealed that 88% (n = 46) found the course useful as it gave a " systematic and schematic " approach enhancing the participants' understanding of reflective practice. Conclusion: The findings suggest that a theoretically informed short course on reflective practice was welcomed by participants who showed a strong interest in learning how to reflect supported by mentors. This pilot provides the basis for further research on reflective practice.